2018
DOI: 10.1136/annrheumdis-2018-213497
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 is an easy to measure biomarker for the interferon signature in systemic lupus erythematosus and antiphospholipid syndrome

Abstract: Galectin-9 is a novel, easy to measure hence clinically applicable biomarker to detect the IFN signature in patients with systemic autoimmune diseases such as SLE and APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 19 publications
4
54
2
Order By: Relevance
“…In patients with juvenile DM, high circulating interferon‐α levels have been found, and in one group of patients with juvenile DM, more than 75% of patients had a positive interferon signature . Circulating galectin‐9 and CXCL10 levels could therefore be a direct reflection of active, interferon‐driven inflammation, which is supported by a recent study in which galectin‐9 was demonstrated to be a marker for the interferon signature in SLE and antiphospholipid syndrome .…”
Section: Discussionmentioning
confidence: 66%
“…In patients with juvenile DM, high circulating interferon‐α levels have been found, and in one group of patients with juvenile DM, more than 75% of patients had a positive interferon signature . Circulating galectin‐9 and CXCL10 levels could therefore be a direct reflection of active, interferon‐driven inflammation, which is supported by a recent study in which galectin‐9 was demonstrated to be a marker for the interferon signature in SLE and antiphospholipid syndrome .…”
Section: Discussionmentioning
confidence: 66%
“…Despite an important role of type 1 IFNs, the direct quantification of type 1 IFNs has been challenging. We focused on Galectin-9, which was shown to be a potential biomarker for the interferon signature [7], with regard to SLE disease activity. The major finding in this study is that circulating levels of Gal-9 are elevated in patients with SLE and are correlated with SLE disease activity and could be a discriminator between SLE patients with and without organ damage distinguished by SLCC Fig 6. Serum levels of Gal-9 in SLE patients with or without active organ involvements.…”
Section: Neuropsychiatric Manifestations and Csf Levels Of Gal-9mentioning
confidence: 99%
“…Surrogate markers for the IFN signature, such as CXCL 10, have been evaluated in SLE patients [5]; however, easy and accurate methods to measure IFN signatures have not been generally established [6]. More recently, Hoogenet et al demonstrated that galactin-9 (Gal-9) is a novel, easy to measure biomarker for type1 IFN signatures and Gal-9 could aid in clinical decision marking in SLE [7]. Gal-9, one of the β-galactoside binding lectins, plays important regulatory roles in autoimmune diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, the evidence is too preliminary to make this determination. Findings of current studies about the role of Gal‐9 in lupus are inconsistent . Van den Hoogen et al showed that serum levels of Gal‐9, CXCL10, and tumor necrosis factor receptor type II (TNFRII) were elevated in patients with SLE and correlated with disease activity and tissue factor expression .…”
mentioning
confidence: 99%
“…Findings of current studies about the role of Gal‐9 in lupus are inconsistent . Van den Hoogen et al showed that serum levels of Gal‐9, CXCL10, and tumor necrosis factor receptor type II (TNFRII) were elevated in patients with SLE and correlated with disease activity and tissue factor expression . Gal‐9 correlated more strongly than CXCL10 or TNFRII with the interferon (IFN) score and was superior to CXCL10 or TNFRII in detecting the IFN signature in patients with SLE, suggesting that it may be a biomarker for SLE .…”
mentioning
confidence: 99%